Efficient Reduction of Nitrobenzene to Aniline with a Biocatalyzed Cathode - Wang, Ai-Jie; Cheng, Hao-Yi; Liang, Bin; Ren, Nan-Qi; Cui, Dan; Lin, Na; Kim, Byung Hong; Rabaey, Korneel (American Chemical Society, 2011)
Nitrobenzene (NB) is a toxic compound that is often found as a pollutant in the environment. The present removal strategies suffer from high cost or slow conversion rate. Here, we investigated the conversion of NB to aniline (AN), a less toxic endproduct that can easily be mineralized, using a fed-batch bioelectrochemical system with microbially catalyzed cathode. When a voltage of 0.5 V was applied in the presence of glucose, 88.2 +/- 0.60% of the supplied NB (0.5 mM) was transformed to AN within 24 h, which was 10.25 and 2.90 times higher than an abiotic cathode and open circuit controlled experiment, respectively. AN was the only product detected during bioelectrochemical reduction of NB (maximum efficiency 98.70 +/- 0.87%), whereas in abiotic conditions nitrosobenzene was observed as intermediate of NB reduction to AN (decreased efficiency to 73.75 +/- 3.2%). When glucose was replaced by NaHCO3, the rate of NB degradation decreased about 10%, selective transformation of NB to AN was still achieved (98.93 +/- 0.77%). Upon autoclaving the cathode electrode, nitrosobenzene was formed as an intermediate, leading to a decreased AN formation efficiency of 71.6%. Cyclic voltammetry highlighted higher peak currents as well as decreased overpotentials for NB reduction at the biocathode. 16S rRNA based analysis of the biofilm on the cathode indicated that the cathode was dominated by an Enterococcus species closely related to Enterococcus aquimarinus.
Keywords: ELECTROCHEMICAL REDUCTION; ENTEROCOCCUS-GALLINARUM; NITROAROMATIC COMPOUNDS; STREPTOCOCCUS-FAECALIS; ELECTRICITY-GENERATION; CELLS; TRICHLOROETHENE; DECHLORINATION; NITROREDUCTASE; NITROCOMPOUNDS